International Network for Genetic Evaluation of Rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Farmers in 22 African countries are planting 83 varieties of rice that originated from the pool of breeding lines shared by rice researchers through the International Network for Genetic Evaluation of Rice (INGER). Thirty-four of the adopted INGER...